Extended Schedule of Heating Regulation: Assessment of - Pyatin A.A.; Suvorov D.M. (Problems of the Regional Energetics, 2020)
The aim of the work is to study the energy efficiency of using an extended schedule of heating regulation when using it for a model district heating system connected to the CHP. The extended schedule of heating regulation ensures the maximum use of the thermal potential of the heat transfer agent and the minimum energy costs for its transport. The assessment of the impact of the extended schedule on the energy efficiency of the CHPP operation was carried out by using an adequate mathematical model of the heat supply system in a generalized form. It was deter-mined that when switching to an extended schedule, the specific energy production for heat consumption in a wide range of changes in the district heating coefficient of a model CHPP in-creases by 1-2% when working on an electrical schedule and by 4-6% when working on a ther-mal schedule. The calculation of the modes of a model CHPP with a fixed design heat load of the CHPP and constant electric power showed that the transition to an extended schedule leads to fuel savings of up to 4.5% during the heating period. Calculations showed that a decrease in heat supply during the transition to new methods of regulation is unprofitable for thermal power plants; therefore, tariffing in the field of thermal energy requires changes, including the transi-tion to two-part tariffs.The results obtained are important for assessing the effectiveness of the transition of heat supply systems to modern schedules of quantitative and qualitative regulation.